Edukasi Kesehatan untuk Pencegahan Stunting pada Ibu dengan Balita 0-24 Bulan di Puskesmas Kapasa - Alfiah A; Uchira Uchira (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting is a serious health problem that affects the physical and cognitive development of children, especially in toddlers aged 0-24 months, with a prevalence that remains high in Indonesia. Community service at the Kapasa Health Centre aims to provide health education to mothers as a strategic step to prevent stunting, using interactive methods and counselling on balanced nutrition and the importance of monitoring child growth. The program has been successful in improving maternal knowledge, with the average score increasing from 34% before the program to 78% after education, demonstrating its effectiveness in changing knowledge of child nutrition. The interactive approach encourages participant engagement, allowing mothers to actively discuss and ask questions, while visual materials reinforce understanding. To effectively combat stunting, education must be complemented by greater knowledge of nutritious foods and by parental monitoring of child growth. Collaboration with local health authorities and community organizations is critical to sustaining these efforts and ensuring that important information reaches more families. Continuous evaluation and adaptive strategies will be essential to expanding the program's reach and effectiveness, ultimately encouraging healthier future generations and contributing significantly to stunting prevention and increased health awareness in the community.